Tiny Low-Power WSN Node for the Vehicle Detection (Informatica, 2014)
In this paper, a tiny low-power wireless sensor network (WSN) node based on msp430 microcontrolleris introduced. The node should be serving the needs of a special WSN used for traffic monitoring, ormore precisely for the indication of vehicle's presence. The single vehicle detection is based on the utilizationof magnetometer sensor, where the change of Earth's magnetic field, caused by the movement ofpassing vehicle, is measured. Communication subsystem of the node is based on the low-power sub-GHztransceiver cc1101 implemented together with the special, energy-efficient communication protocol in 868MHz ISM band. In line with low-power architecture, environment friendly power consumption of the nodewas reached. It is equal on average to 300uA, when transmitting period is 1s and magnetometer data collectionrate is equal to 20Hz.